2016
DOI: 10.1186/s12915-016-0279-9
|View full text |Cite
|
Sign up to set email alerts
|

Global identification of hnRNP A1 binding sites for SSO-based splicing modulation

Abstract: BackgroundMany pathogenic genetic variants have been shown to disrupt mRNA splicing. Besides splice mutations in the well-conserved splice sites, mutations in splicing regulatory elements (SREs) may deregulate splicing and cause disease. A promising therapeutic approach is to compensate for this deregulation by blocking other SREs with splice-switching oligonucleotides (SSOs). However, the location and sequence of most SREs are not well known.ResultsHere, we used individual-nucleotide resolution crosslinking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 96 publications
8
67
0
Order By: Relevance
“…Quantitative sequence specificity modeling of the resulting distribution of binding affinities allowed the intrinsic determinants of hnRNP A1 recognition to be identified. HnRNP A1 is generally characterized as nonspecific owing to its wide range of cellular functions; however, crosslinking immunoprecipitation (CLIP) and RNAcompete studies identified similar consensus patterns that center around a composite UAGG motif (11,24,34). Consistent with those results, the highest affinity SL3 ESS3 variant identified from HTS-EQ has a GUAGGAG sequence and 76% of the top 50 variants all contain UAG.…”
Section: Ess3supporting
confidence: 71%
See 1 more Smart Citation
“…Quantitative sequence specificity modeling of the resulting distribution of binding affinities allowed the intrinsic determinants of hnRNP A1 recognition to be identified. HnRNP A1 is generally characterized as nonspecific owing to its wide range of cellular functions; however, crosslinking immunoprecipitation (CLIP) and RNAcompete studies identified similar consensus patterns that center around a composite UAGG motif (11,24,34). Consistent with those results, the highest affinity SL3 ESS3 variant identified from HTS-EQ has a GUAGGAG sequence and 76% of the top 50 variants all contain UAG.…”
Section: Ess3supporting
confidence: 71%
“…Selection amplification experiment(s) (SELEX) identified a high-affinity motif 5′-UAGGGA/U-3′ that now serves as a benchmark for sequence-specific hnRNP A1 binding (23). Transcriptome-wide studies of functional hnRNP A1 binding sites using motif finder algorithms further indicate specificity for a 5′-UAG-3′ motif (11,24). In previous work, we determined a small angle X-ray scattering (SAXS) model of UP1 in complex with the HIV ESS3 stem loop (SL3 ESS3 ), which was guided by a 1.92-Å crystal structure of UP1 bound to a 5′-AGU-3′ oligomer (25).…”
mentioning
confidence: 99%
“…First, both RRMs have a preference for the 5´-UAGG-3´ motif, which was indeed present in many RNAs found by SELEX or iCLIP (Burd and Dreyfuss, 1994; Bruun et al, 2016). Second, both RRMs are tolerant to accommodate a cytosine 5´ to the AG core, extending the recognition motif to 5´-U /C AGG-3´.…”
Section: Resultsmentioning
confidence: 90%
“…Interestingly, motifs of in vivo targets of hnRNP A1 can be fairly different (see for instance the ISS-N1 binding sites 5´-CAGCAU-3´ and 5´-UGAAAG-3´ in the context of SMN pre-mRNAs [Hua et al, 2008] or the binding sites in SKA2 exon 3 recently identified by iCLIP [Bruun et al, 2016]).…”
Section: Resultsmentioning
confidence: 99%
“…A point mutation at position 6 in exon 7 of SMN2 eliminates an exonic splicing enhancer (ESE) recognized by serine/arginine-rich splicing factor 1 (SRSF1) (5,6) and creates an exonic splicing silencer (ESS) recognized by heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) (7). This ESS acts synergistically with other ESS motifs that bind to hnRNP A1 and Sam68, and repress exon 7 inclusion (811). This leads to the production of a truncated and unstable protein (12).…”
Section: Introductionmentioning
confidence: 99%